Barbara Jordan : speaking the truth with eloquent thunder - Jordan, Barbara, 1936-1996 (Louann Atkins Temple women & culture series ;, 2007)
"Revered by Americans across the political spectrum, Barbara Jordan was "the most outspoken moral voice of the American political system," in the words of former President Bill Clinton, who awarded her the Presidential Medal of Freedom in 1994. Throughout her career as a Texas senator, U.S. congresswoman, and distinguished professor at the Lyndon B. Johnson School of Public Affairs, Barbara Jordan lived by a simple creed: "Ethical behavior means being honest, telling the truth, and doing what you said you were going to do." Her strong stand for ethics in government, civil liberties, and democratic values still provides a standard around which the nation can unite in the twenty-first century. This volume brings together several major political speeches that articulate Barbara Jordan's most deeply held values. They include: "Erosion of Civil Liberties," a commencement address delivered at Howard University on May 12, 1974, in which Jordan warned that "tyranny in America is possible" "The Constitutional Basis for Impeachment," Jordan's ringing defense of the U.S. Constitution before the House Judiciary Committee investigating the Watergate break-in Keynote addresses to the Democratic National Conventions of 1976 and 1992, in which Jordan set forth her vision of the Democratic Party as an advocate for the common good and a catalyst of change Testimony in the U.S. Congress on the confirmation of Supreme Court nominee Robert Bork and on immigration reform Meditations on faith and politics from two National Prayer Breakfasts Acceptance speech for the 1995 Sylvanus Thayer Award presented by the Association of Graduates of the United States Military Academy, in which Jordan challenged the military to uphold the values of "duty, honor, country" Accompanying the speeches, some of which readers can also watch on an enclosed DVD, are context-setting introductions by volume editor Max Sherman. The book concludes with the eloquent eulogy that Bill Moyers delivered at Barbara Jordan's memorial service in 1996, in which he summed up Jordan's remarkable life and career by saying, "Just when we despaired of finding a hero, she showed up, to give the sign of democracy. ... This is no small thing. This, my friends, this is grace. And for it we are thankful." .. From publisher's description